Comparison of the Real Part of Dielectric Constants with Different Materials to Decrease the Emittance and a Virtual Dielectric Constant to Reproduce Reflectance - Jesús Manuel Gutiérrez-Villarreal; Horacio Antolin Pineda-León; Mario F. Suzuki Valenzuela; Ian Sosa-Tinoco; Santos Jesús Castillo (Photonics, 2023)
This paper analyzes how the real part of the dielectric constant affects the emittance or temperature in some materials. A two-layer configuration was implemented on a glass substrate, with theory and experiment, on a sunny day in Mexico. Furthermore, the transfer matrix method was used as theory, changing the material on the top of the substrate and below a film of zinc sulfide. As a result, for a larger real part of the dielectric constant, the emittance decreased in analytical results, and therefore a decrease in temperature was obtained in the experiment. Furthermore, a virtual dielectric constant was obtained from the experimental reflectance in a bilayer system reproducing this system analytically with one layer having different thickness. The finite-difference time-domain (FDTD) method was used to obtain the optimal length of equilateral pyramids on the surface of a flat film by changing the materials to improve the reflectance or decrease the emittance. It was concluded that for a wavelength of the incident source, optimal dimensions of the triangles on the surface exist.